Solar Power Plant (PLTS) Power Monitoring System Based on the Internet of Things (IoT) Using the Blynk and Telegram Platforms - Madjowa, Tyo Sulistio; Ilham, Jumiati; Hidayat, Ikhsan; Abdussamad, Salmawaty Tansa , Syahrir; Z. Nasibu, Iskandar (Emitor: Jurnal Teknik Elektro, 2026)
Solar energy is one of the renewable energy sources that has the potential to be developed in Indonesia. However, monitoring the performance of Solar Power Plants (PLTS) is generally still carried out conventionally so that the data obtained is not real-time and makes it difficult to detect disturbances. The Internet of Things (IoT) based PLTS electric power monitoring system is designed to monitor electrical parameters in real-time, including voltage, current, power, temperature, and humidity. The system design uses PZEM-004T, PZEM-017, and DHT11 sensors integrated with an ESP32 microcontroller as the main controller. The measurement data is displayed on an OLED screen and sent to the Blynk and Telegram applications as remote monitoring media with an automatic notification feature. The test results show that the system works well and has a high level of accuracy. During daytime testing, the highest DC and AC voltage values were recorded at 18.22 V and 233.8 V, respectively, while at night they reached 12.36 V and 228.1 V. The maximum DC current and power values were 0.44 A and 7.9 W, respectively. Comparison with manual measuring instruments showed very small measurement differences, namely 0.01–0.05 V for DC voltage and 0.1% for humidity, with an average error of only 0.07%. These findings prove that the developed IoT-based monitoring system is stable, accurate, and efficient in monitoring the condition of the solar power plant in real-time, and has the potential to be further developed on a larger scale through the integration of cloud storage and intelligent energy management.